Determinasi E-WOM Terhadap Reputasi Merek dan Kinerja Bisnis pada Ekosistem Social Commerce - Fitri Yutika (Jurnal Manajerial, 2026)
Background – The emergence of TikTok Shop has shifted consumer trust from formal ads to peer-driven validation through Electronic Word of Mouth (e-WOM). Understanding this digital phenomenon is crucial as reputation now stems from continuous social interactions. Aim – This study analyzes e-WOM's influence on Brand Reputation and Business Performance within TikTok Shop using Resource-Based View (RBV) and Marketing Productivity theories. Methodology – A quantitative approach using SEM-PLS was applied to data from 155 active TikTok Shop users, predominantly Gen Z (63%), collected via purposive sampling. Findings – The analysis reveals that e-WOM has a positive and significant impact on Brand Reputation and Business Performance. These results confirm that digital validation serves as a primary trust signal that builds brand equity before driving economic outcomes. This evidence proves that in social commerce, reputation acts as a strategic gateway to market growth and long-term customer loyalty. Conclusion - This study concludes that e-WOM is the most dominant determinant of brand reputation within the TikTok Shop ecosystem. The high correlation between e-WOM and reputation suggests that for Gen Z, peer-driven credibility is more influential than formal advertising. Therefore, achieving a strong digital reputation through organic social interaction is a mandatory prerequisite for optimizing business performance in the social commerce era. Research implication – Theoretically, it reinforces digital reputation as a strategic intangible asset. Managerially, businesses must prioritize "authenticity over formality" in affiliate content and implement real-time sentiment management to maintain relationship quality with the dominant Gen Z market.   Limitations – This research is limited by its focus on a single platform (TikTok Shop) and a specific demographic (mostly students). Future studies should explore cross-platform dynamics and include additional variables such as FOMO or Price Sensitivity to broaden the understanding of business performance drivers.